ANÁLISE ESPACIAL DOS IDOSOS CADASTRADOS PELA ESTRATÉGIA DE SAÚDE DA FAMÍLIA EM SÃO LUÍS-MA. - MARTINS, Érica Silva (2016)
Objective: To analyze the spatial form, the situation of elderly people registered by the Family Health Strategy and residents between the health districts of São Luís - MA, in 2004 and 2014. Methodology: This is a descriptive study, which ecological character exploratory with a quantitative approach. Had as population, elderly registered on the platform of the Information Primary Care System (SIAB), the ESF and residents by districts according to the IBGE (2000 and 2010). The variables used were selected using data collected in the "FORM A" on the number of registered elderly by health district, elderly residents and health characteristics as water supply, sewage system and garbage collection, according to IBGE. Secondary data were processed using GIS software in QGIS 2.8, we obtained the population density of the elderly, the attendance rate of registered elderly and health characteristics by district. Results: The district with the highest rate of elderly registered in 2004, was Vila Hope with 92.7%, remaining in 2014 with 72%. The district lower rate of registered elderly was the Centre with 19% in 2004, in 2014 the lowest rate was in Bequimão district was 32%, followed by the Centre with 38%. As the health characteristics, the Hope Village District in 2000, had the lowest percentage representative to these conditions, and 6% of sewage and 41.6% of waste collected. The Center presented satisfactory rates of 94.81% of water, 75.87% of sewage network and 76% of waste collected. In 2010, Vila Hope remained low percentages with 44% of water, 5% for sewerage and 49.77% of waste collected, while the center of the district showed that its percentage remained, indicating 92% , 78.32% and 98% respectively. Conclusion: no convergence between the data of residents and registered elderly may be compromising the health of the general population and especially the elderly.